Estimates for the Rate of Convergence in Ordinary Differential Equations under the Action of Random Processes with Fast Time - Bondarev, B. V.; Kovtun, E. E. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We study the procedure of averaging in the Cauchy problem for an ordinary differential equation perturbed by a certain Markov ergodic process. We establish several estimates for the rate of convergence of solutions of the original problem to solutions of the averaged one.